miR-21-5p Targets PIK3R1 to Regulate the NF-κB Signaling Pathway, Inhibiting the Invasion and Progression of Prolactinoma - Min de Li; Juan Yang; Xiao Wu; Shang Si Chen (International Journal of Endocrinology)
Prolactinomas (PRLs) are benign tumors with malignant characteristics that can invade the surrounding tissue structures and are challenging to treat. It has been reported that miR-21-5p expression in pituitary adenomas is correlated with tumor invasion and size. However, the mechanism of action of miR-21-5p in PRL remains unclear. Dysregulation of the phosphoinositide-3-kinase (PI3K) regulatory Subunit 1 pathway occurs frequently in cancer and plays an important role in tumor progression as an important component of the PI3K pathway. However, the role of PIK3R1 in PRL and its regulatory mechanism are unknown. In this study, we first explored the effect of miR-21-5p in PRL and then confirmed that PIK3R1 is a direct target of miR-21-5p using bioinformatics and cellular experiments. Subsequent in vitro experiments demonstrated that overexpression of PIK3R1 significantly attenuated the biological effects of miR-21-5p in PRL cells, such as promoting proliferation and invasion. Finally, we explored the mechanism by which PIK3R1 affects PRL progression and found that the inhibition of IκBa degradation by PIK3R1 impacts PRL progression via the miR-21-5p/PIK3R1/MMP pathway.